2020
DOI: 10.3390/ijerph17072563
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Patterns of the 2019-nCoV Epidemic at the County Level in Hubei Province, China

Abstract: Understanding the spatio-temporal characteristics or patterns of the 2019 novel coronavirus (2019-nCoV) epidemic is critical in effectively preventing and controlling this epidemic. However, no research analyzed the spatial dependency and temporal dynamics of 2019-nCoV. Consequently, this research aims to detect the spatio-temporal patterns of the 2019-nCoV epidemic using spatio-temporal analysis methods at the county level in Hubei province. The Mann-Kendall and Pettitt methods were used to identify the tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 28 publications
2
49
0
1
Order By: Relevance
“…Effectively using the results from the planning tool to inform actions could mean the difference between suppressing the virus and allowing it to re-emerge. In comparison, it is noted that studies that map the geospatial spread of coronavirus from Wuhan to neighboring communities are starting to emerge [ 59 , 60 ], and similar efforts need to be launched in the U.S. The application of geospatial methods to case data enables significantly more rigor in understanding the confluence of various factors that jointly increase vulnerabilities and reduce resilience to COVID-19 spread, impact, re-emergence in new hot spots or on a seasonal basis.…”
Section: Discussionmentioning
confidence: 99%
“…Effectively using the results from the planning tool to inform actions could mean the difference between suppressing the virus and allowing it to re-emerge. In comparison, it is noted that studies that map the geospatial spread of coronavirus from Wuhan to neighboring communities are starting to emerge [ 59 , 60 ], and similar efforts need to be launched in the U.S. The application of geospatial methods to case data enables significantly more rigor in understanding the confluence of various factors that jointly increase vulnerabilities and reduce resilience to COVID-19 spread, impact, re-emergence in new hot spots or on a seasonal basis.…”
Section: Discussionmentioning
confidence: 99%
“…The response options are: 3 = nearly every day, 2 = more than half the days, 1 = several days, and 0 = not at all for PHQ-9 and GAD-7; 4 = always, 3 = often, 2 = sometimes, 1 = rare, and 0 = never for ISI-7 and IES-7. The total scores of these survey scales are interpreted as follows: PHQ-9, extremely severe (22-28), severe (15)(16)(17)(18)(19)(20)(21), moderate (10)(11)(12)(13)(14), mild (5)(6)(7)(8)(9), and normal (0-4) depression; GAD-7, severe (15)(16)(17)(18)(19)(20)(21), moderate (10)(11)(12)(13)(14), mild (5)(6)(7)(8)(9), and normal (0-4) anxiety; ISI-7, severe (22-28), moderate (15)(16)(17)(18)(19)(20)(21), subthreshold (8)(9)(10)(11)(12)(13)…”
Section: Mental Health Problemsmentioning
confidence: 99%
“…Massaro and Kondor [14] studied the interaction between human mobility and outbreaks of infectious diseases and found that intra-city human mobility is a major factor in the spread of infectious diseases in Singapore. Some studies have analyzed the spatiotemporal pattern of COIVD-19 at the national or district levels [1,15,16]. However, few studies have examined the relationship between human movement and the spatiotemporal distribution of infectious diseases at the national scale because it is difficult to obtain detailed intercity travel records [17].…”
Section: Human Mobility and Infectious Diseasesmentioning
confidence: 99%